Poisonous insects - Ballard, Walter Raymond (My University, 1905)
Introduction: The poison of insects is for the purpose of protecting them from their enemies and of securing food either for themselves or their larvae. The subject is important to us at present in its relation to the higher animals. Either from accident or in the performance of ordinary work, many persons become painfully conscious of the irritating effect of insect poisons. A knowledge of those species which are poisonous would in many cases preclude much of the suffering from this source. The present article is simply an attempt to compile the literature on the subject in a convenient from. Unfortunately the literature is much scattered and largely inaccessible, so that at best this work can be only incomplete.
Citation: Ballard, Walter Raymond. Poisonous insects. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Classes of poisonous insects; Stinging Insects; Stinging Larvae; Theses; Manuscripts (documents)